PENGARUH DISRUPTIVE INNOVATION DAN KUALITAS STRATEGI PEMASARAN TERHADAP KEUNGGULAN BERSAING - Bayu Sapta Adi Nugroho; Natoil Natoil (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract This study aims to examine the effect of disruptive innovation and the quality of marketing strategies and their impact on competitive advantage. The problem in this research is how to increase competitive advantage.In this study, the population used were all 100 online shop sellers in Semarang. Regression analysis was carried out with Statistical Package Social Science (SPSS) software, which was used to analyze the data. The results of the analysis showed that disruptive innovation and the quality of marketing strategies had a significant effect on competitive advantage.These empirical findings indicate that disruptive innovation and the quality of marketing strategies have a significant effect on competitive advantage.